iBoccia: a framework to monitor the Boccia gameplay in elderly - Silva, Vinicius Corrêa Alves (2018)
The increase of the elderly population has an enormous effect on the health care system of a country, as the rise of this population sets the mood to an exponential growth in assistance and care. Indeed, the inherent costs of this populational class are higher when comparing to the younger classes. Today paradigm focuses on the reduction of these costs by promoting a healthier lifestyle on all classes of the populations. Thus, the concern of a more active lifestyle is present in the elderly population, which has proven to reduce, for example, the risk of coronary problems. The stimulus on physical activity is now higher and it is possible to get several monitoring devices to keep track on the activity that was performed. Following this trend, the present paper presents a hybrid approach that employs the use of wearable devices, the Mio Fuse band and the pandlet, and a non-wearable device, the Kinect camera, to monitor elderly people during a Boccia game scenario. Preliminary tests were performed in laboratory. The results include data collected concerning a main movement that is used during a Boccia gameplay.